2017
DOI: 10.1002/jmri.25803
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of olfactory neuroblastomas from nasal squamous cell carcinomas using MR diffusion kurtosis imaging and dynamic contrast‐enhanced MRI

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:354-361.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…33 Thus, a high K value may be an efficient indicator of lymphomas. Additionally, ONBs also showed high K values in our cohort, which was in good agreement with a previous study reported by Xiao et al 34 This finding can be explained by the complex microstructure of ONBs, because ONBs are usually separated by the fibrous, vascular, or inflammatory stroma to form the nested appearance within the tumor. Notably, although necrosis and hemorrhage are often respectively seen in SCCs and MMs with increased K values, our results indicated that the K values (complexity) of these two entities were much lower than those of lymphomas and ONBs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…33 Thus, a high K value may be an efficient indicator of lymphomas. Additionally, ONBs also showed high K values in our cohort, which was in good agreement with a previous study reported by Xiao et al 34 This finding can be explained by the complex microstructure of ONBs, because ONBs are usually separated by the fibrous, vascular, or inflammatory stroma to form the nested appearance within the tumor. Notably, although necrosis and hemorrhage are often respectively seen in SCCs and MMs with increased K values, our results indicated that the K values (complexity) of these two entities were much lower than those of lymphomas and ONBs.…”
Section: Discussionsupporting
confidence: 93%
“…Some patients in the present study cohort overlapped those of our previous studies. 17,26,30,31,34,45 In those studies, we used conventional DWI, IVIM, and DKI with ROI measurements to differentiate benign from malignant sinonasal lesions, to differentiate sinonasal SRCMTs from non-SRCMTs, to differentiate olfactory neuroblastomas from nasal squamous cell carcinomas and to correlate different DWI parameters with Ki-67 labeling index.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients in the present study cohort overlapped those of our previous studies . In those studies, we used conventional DWI, IVIM, and DKI with ROI measurements to differentiate benign from malignant sinonasal lesions, to differentiate sinonasal SRCMTs from non‐SRCMTs, to differentiate olfactory neuroblastomas from nasal squamous cell carcinomas, and to correlate different DWI parameters with Ki‐67 labeling index.…”
Section: Acknowledgementmentioning
confidence: 89%
“…D app is the diffusion coefficient with correction of ADC value for non-Gaussian bias, which shows inverse correlation to tumor cellular density (21,22). In subgroup analyses, among three most common parotid gland tumors, consistent with previous studies (23), Warthin’s tumors showed the lowest diffusion value of 0.808 ± 0.227 × 10 −3 mm 2 /s, followed by malignant tumors of 0.937 ± 0.250 × 10 −3 mm 2 /s and pleomorphic adenomas of 1.525 ± 0.396 × 10 −3 mm 2 /s, despite the difference between Warthin’s tumors and malignant tumors not reaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%